2013
DOI: 10.1590/s1981-67232013005000016
|View full text |Cite
|
Sign up to set email alerts
|

Tempo de cozimento e textura de raízes de mandioca

Abstract: ResumoO objetivo deste trabalho foi avaliar a adequação de medidas instrumentais de textura como índice de qualidade de raízes da mandioca de mesa e sua correlação com o tempo de cozimento. Quinze raízes de mandioca foram colhidas no 11.º mês de cultivo na região noroeste fluminense. Pedaços de raízes foram cozidos em água, sendo o tempo de cozimento determinado, em triplicata, quando se observou pouca resistência à penetração do garfo. A resistência ao corte foi realizada nas polpas cruas e cozidas, em cinco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
3
14

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 7 publications
3
13
3
14
Order By: Relevance
“…Variation was within the time range obtained in this study (14.67 to 25.33 minutes), which is within the acceptable limit to market cassava for food, 30 minutes (Fukuda et al, 2002). However, Talma et al (2013) stated that the lower the cooking time, the better the mass quality, considering between 15 and 25 minutes as the optimal time.…”
Section: Ascorbic Acid and Cooking Timesupporting
confidence: 76%
“…Variation was within the time range obtained in this study (14.67 to 25.33 minutes), which is within the acceptable limit to market cassava for food, 30 minutes (Fukuda et al, 2002). However, Talma et al (2013) stated that the lower the cooking time, the better the mass quality, considering between 15 and 25 minutes as the optimal time.…”
Section: Ascorbic Acid and Cooking Timesupporting
confidence: 76%
“…As raízes de mandioca apresentaram tempo de cocção entre 20 e 34 minutos (Tabela 2), sendo 30 minutos o tempo máximo aceitável para raízes de mandioca de mesa. Quanto menor for o tempo de cozimento, melhor será a qualidade da massa gerada (TALMA et al, 2013). Além disso, o baixo tempo de cozimento gera economia de energia e de ocupação, sendo uma característica desejada pelo consumidor final (MORETO; NEUBERT, 2014).…”
Section: Diasunclassified
“…Such a result is supported by Mezette et al (2009) and Pereira et al (1985) who reported a strong relation between the cooking time of cassava roots and their texture, stickiness and plasticity. According to Talma et al (2013), the lower the cooking time, the better the quality of the cooked pasta. Table 3 shows the analysis of variance analysis for starch, amylose, amylopectin, crude protein and ash contents.…”
Section: Root Pulpmentioning
confidence: 99%